The relationship of oral reading fluency endurance to comprehension in an intermediate depth orthography - Cadime, Irene Maria Dias (2023)
One-minute oral reading fluency (ORF) tests are widely used, but concerns have been raised regarding whether readers are able to maintain their performance if asked to read for a larger period. The main goals of this study were to investigate whether students are able to maintain their ORF performance in a three-minute task and whether scores measured at one and at three minutes are equally good predictors of the performance in a standardized reading comprehension measure. The sample was composed of 159 Portuguese primary school students (grades 2-4). The results suggested that the number of words read correctly (WRC) declined across reading time and that three-minute mean score underestimated fluency in all grade levels compared to a one-minute reading score. The WRC measured either at one minute or using a three-minute average score was an equal predictor of reading comprehension in all grades. Implications for theory and practice are discussed.